THE LEVEL OF ACHIEVEMENT OF GRADUATES OF DENTAL MASTER'S PROGRAMS BASED ON THE RESULTS OF THEIR CERTIFICATION AT EC30. PEDIATRIC THERAPEUTIC DENTISTRY IN MODERN CONDITIONS - L.F. Kaskova; L.P. Ulasevych; L.I. Amosova; O.S. Pavlenkova; S.Ch. Novikova; O.V. Khmil; M.O. Sadovski (Український стоматологічний альманах, 2024)
Aims and objectives. To analyze the preparation of second-cycle (master's) degree students in the Educational-Professional Program "Dentistry" in the discipline "Pediatric Therapeutic Dentistry" based on the results obtained during the final state certification examination using the Objective Structured Practical (Clinical) Examination.